Functional and sensory properties of toasted tortillas are shaped by structural changes in native maize starch - Palacios-Pola, Gabriela; Perales, Hugo R.; Figueroa Cárdenas, Juan de Dios; Abud-Archila, Miguel; Escalante-Aburto, Anayansi; Álvarez Rateike, Lurline; Bolom Martínez, Susana Del Carmen; Lagunes Quevedo, Verónica (Frontiers in Nutrition, 2025)
The majority of maize-based foods are produced via nixtamalization, which includes toasted tortillas (tostadas). Women artisanal producers in Chiapas, Mexico, have refined key quality parameters, such as texture and resistant starch content, by using native maize varieties that preserve traditional traits. Nixtamalization modifies maize functionality through the formation of resistant starch, which resists digestion and supports beneficial colonic microbiota via short-chain fatty acid production. This study aimed to evaluate the functional, sensory, and structural properties of tostadas that were prepared via two cooking processes using native maize from Chiapas. In this research, starch gelatinization was achieved through three different processes: traditional nixtamalization (control), short boiling, and full boiling. The resulting tostadas were: nixtamalized corn tostadas (NCT), partially-burst tostadas (PBT), and fully-burst tostadas (FBT), respectively. Tostada sensory attributes were analyzed by a trained panel that assessed multiple parameters, namely crunchiness, fracturability, hardness, corn aroma, nixtamal aroma, corn taste, nixtamal taste, and stickiness. On the other hand, consumer testing was used to evaluate chewing parameters. Partially-burst tostada (PBT) and fully-burst tostada (FBT) exhibited structural, functional, and sensory properties that are associated with the sensation of satiety and liking. Corn races did not have a statistically significant effect on the rheological or sensory properties of tostadas. However, the nixtamalization method significantly influenced stickiness and taste parameters. Stickiness intensity (4.50) and eating rate (62.66 g/min) for FBT were statistically different from PBT’s respective values (3.75 and 56.12 g/min). These characteristics favor the chewing process. When maize is cooked for longer periods, the peak of amylose–lipid complexes is more easily detected. Resistant starch in FBT was higher (5.6%) than in PBT and NCT, which were 3.7% and 2.4%, respectively. Key tostada quality parameters, such as chewiness and sensory characteristics, correlated well with the structural and rheological properties of the modified starch (partial gelatinization) formed during tostada preparation.